A Novel Multi-domain High Molecular, Salt-Stable Alkaline Xylanase from Alkalibacterium sp. SL3 - Wang, Guozeng; Wu, Jingjing; Yan, Renxiang; Lin, Juan; Ye, Xiuyun (Frontiers in Microbiology, 2017)
A novel multi-domain high molecular xylanase coding gene (xynSL3) was cloned from Alkalibacterium sp. SL3, an alkaliphilic bacterial strain isolated from the sediment of soda lake Dabusu. The deduced XynSL3 is composed of a putative signal peptide, three tandem domains of carbohydrate binding module (CBM) family 22, a catalytic domain of glycosyl hydrolase (GH) family 10 and a domain of CBM9. XynSL3 shares the highest identity of 66% to a hypothetical protein from Alkalibacterium sp. AK22 and has low identities (33%-45%) with other functionally characterized xylanases. The gene xynSL3 was expressed heterologously in Escherichia coli and the recombinant enzyme demonstrated some particular characteristics. Purified recombinant XynSL3 (rXynSL3) was highly active and stable over the neutral and alkaline pH ranges from 7.0 to 12.0, with maximum activity at pH 9.0 and around 45% activity at pH 12.0. It had an apparent temperature optimum of 55°C and was stable at 50°C. The rXynSL3 was highly halotolerant, retaining more than 60% activity with 3 M NaCl and was stable at up to a 4 M concentration of NaCl. The hydrolysis products of rXynSL3 from corncob xylan were mainly xylobiose and xylotetraose. The activity of rXynSL3 was enhanced by Ca2+ and it has strong resistance to sodium dodecyl sulfate (SDS). This multi-domain, alkaline and salt-tolerant enzyme has great potential for basic research and industrial applications such as the biobleaching of paper pulp and production of xylo-oligosaccharides (XOS).